Prevalence Of Anthracnose In Mango Nurseries Of Punjab (Journal of Plant Disease Sciences, 2020)
Anthracnose caused by Colletotrichum gloeosporioides is a devastating pre and post-harvest disease of mango causing huge losses in mango production. To determine the prevalence of anthracnose of mango in nursery the survey was conducted in Gurdaspur, Hoshiarpur and Pathankot districts of Punjab state during April-May and August-September, 2017 and 2018. Different mango nurseries of 1-2 year old plants were visited for recording disease incidence and percent disease index on different varieties. Maximum average disease incidence up to 43.36 per cent was recorded at Pathankot district, followed by Gurdaspur and Hoshiarpur with average disease incidence ranging from 42.63 and 39.22 per cent, respectively. Among different varieties, average disease incidence was maximum (46.33) in the variety Malika with disease index of 37.17 per cent whereas the variety Baramasi showed minimum average disease incidence (33.76%) and disease index (20.91%). The pathogen was isolated from diseased leaf samples of mango nursery and identified as Colletotrichum gloeosporioides.
Keywords: Mango; Variety; Anthracnose; Colletotrichum gloeosporioides; Prevalence